Construction of a Live-Attenuated Vaccine Strain of Yersinia pestis EV76-B-SHUΔpla and Evaluation of Its Protection Efficacy in a Mouse Model by Aerosolized Intratracheal Inoculation - Feng, Junxia; Deng, Yingying; Fu, Mengjiao; Hu, Xueyuan; Luo, Wenbo; Lu, Zhiyu; Dai, Lupeng; Yang, Huiying; Zhao, Xiaodong; Du, Zongmin; Wen, Bohai; Jiang, Lingxiao; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Plague, which is caused by Yersinia pestis, is one of the most dangerous infectious diseases. No FDA-approved vaccine against plague is available for human use at present. To improve the immune safety of Y. pestis EV76 based live attenuated vaccine and to explore the feasibility of aerosolized intratracheal inoculation (i.t.) route for vaccine delivery, a plasminogen activator protease (pla) gene deletion mutant of the attenuated Y. pestis strain EV76-B-SHU was constructed, and its residual virulence and protective efficacy were evaluated in a mouse model via aerosolized intratracheal inoculation (i.t.) or via subcutaneous injection (s.c.). The residual virulence of EV76-B-SHUΔpla was significantly reduced compared to that of the parental strain EV76-B-SHU following i.t. and s.c. infection. The EV76-B-SHUΔpla induced higher levels of mucosal antibody sIgA in the bronchoalveolar lavage fluid of mice immunized by i.t. but not by s.c.. Moreover, after lethal challenge with Y. pestis 201, the protective efficacy and bacterial clearance ability in the EV76-B-SHUΔpla-i.t. group were comparable to those of the EV76-B-SHUΔpla-s.c. and EV76-B-SHU immunized groups. Thus, the EV76-B-SHUΔpla represents an excellent live-attenuated vaccine candidate against pneumonic plague and aerosolized i.t. represents a promising immunization route in mouse model.